A STUDY OF WRITING TASKS IN THE NMET 2014 - Lin Dunlai (University of Kuningan, 2014)
Abstract:Â The National Matriculation English Test (NMET) is a high-stakes test compulsory for those aspiring to entering higher education institutions in China. The test is designed by the National Education Examinations Authority (NEEA) and some local examination authorities. The final section of this test is generally a writing task. In this paper, the author examines the 21 writing tasks that were used in the NMET 2014. Using content analysis, and a priori validation components of Weirâ€™s (2005) socio-cognitive validation framework, namely test taker characteristics, cognitive validity and context validity, the paper finds out the merits and demerits of these 21 writing tasks. It is concluded that these writing tasks are generally well designed and are valid in helping select talents. But more empirical research must be done to investigate how the writing tasks function for students when taking these writing tests.Keywords: NMET, socio-cognitive validation framework, cognitive validity, context validity, China